Variability in Motivational Interviewing Adherence Across Sessions, Providers, Sites, and Research Contexts - Hallgren, Kevin A. (J Subst Abuse Treat, 2017)
Providers’ adherence in the delivery of behavioral interventions for substance use disorders is not fixed, but instead can vary across sessions, providers, and intervention sites. This variability can substantially impact the quality of intervention that clients receive. However, there has been limited work to systematically evaluate the extent to which substance use intervention adherence varies from session-to-session, provider-to-provider, and site-to-site. The present study quantifies the extent to which adherence to Motivational Interviewing (MI) for alcohol and drug use varies across sessions, providers, and intervention sites and compares the extent of this variability across three common MI research contexts that evaluate MI efficacy, MI effectiveness, and MI training. Independent raters coded intervention adherence to MI from 1275 sessions delivered by 216 providers at 15 intervention sites. Multilevel models indicated that 57%–94% of the variance in MI adherence was attributable to variability between sessions (i.e., within providers), while smaller proportions of variance were attributable to variability between providers (3%–26%) and between intervention sites (0.1%–28%). MI adherence was typically lowest and most variable within contexts evaluating MI training (i.e., where MI was not protocol-guided and delivered by community treatment providers) and, conversely, adherence was typically highest and least variable in contexts evaluating MI efficacy and effectiveness (i.e., where MI was highly protocolized and delivered by trained therapists). These results suggest that MI adherence in efficacy and effectiveness trials may be substantially different from that obtained in community treatment settings, where adherence is likely to be far more heterogeneous.